Sentenças interpretativas, coisa julgada e súmula vinculante: alcance e limites dos efeitos vinculante e erga omnes na jurisdição constitucional - Abboud, Georges (2009)
The present work aims to examine the principle procedural aspects related to the unconstitutional decision. Thus, the following institutes will be explained: claim preclusion (res judicata), erga omnes effect and binding effect. All of them will be explained and compared with the similar effects of the comparative law. After identifying these effects and demonstrating their differences, we will examine how they affect the different types of unconstitutional decisions. Therefore, the interpretative, manipulative and restrictive decisions will be discussed. Finally, we will examine the recent institute of abridgment of law, showing what the similarities and differences in relation to the decisions in the concentrated control of constitutionality